Prevalence of gastrointestinal complications in patients with type 2 diabetes mellitus in Iran: a systematic review and meta-analysis - Kazeminia, Mohsen; Salari, Nader; Shohaimi, Shamarina; Akbari, Hakimeh; Mohammadi, Masoud (Springer Science and Business Media LLC, 2022)
Background Type 2 diabetes is the most common diabetes in the world and constitutes a high percentage of diabetes cases. This study aims to determine the overall prevalence of gastrointestinal complaints in Iranian patients with type 2 diabetes.